2017
DOI: 10.14236/ewic/hci2017.7
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Children’s Search Query Formulation Habits

Abstract: The strategies children use for digital information search in educational settings are rarely explored. Open questions remain on such fundamental issues as to which information-seeking strategies children employ, how they construct queries, and if the strategies that are taught are effective when using modern search engines. We conducted an observation study with school children to gain insights into these questions. As a result of this study, we identified query-creation and query-reformulation strategies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 8 publications
(16 reference statements)
1
18
0
5
Order By: Relevance
“…Given the speed of technology evolution, much of the existing research into children's information seeking and use is somewhat dated, and very few investigations into children's information seeking have appeared in the last 5 years. Among the more recent works, we find researchers have investigated children's search performance on commercial search engine interfaces designed for children (Jochmann-Mannak, Huibers, Lentz, & Sanders, 2010;Vanderschantz & Hinze, 2017) as well as on research led search user interfaces for children (Gossen, Nitsche, & Nürnberger, 2012;Vanderschantz & Hinze, 2018), and in the home (e.g., Druin, Foss, Hutchinson, Golub, & Hatley, 2010), but little education or classroom based investigations of what and how children are interacting with technologies.…”
Section: Children's Information Seeking and Usementioning
confidence: 99%
“…Given the speed of technology evolution, much of the existing research into children's information seeking and use is somewhat dated, and very few investigations into children's information seeking have appeared in the last 5 years. Among the more recent works, we find researchers have investigated children's search performance on commercial search engine interfaces designed for children (Jochmann-Mannak, Huibers, Lentz, & Sanders, 2010;Vanderschantz & Hinze, 2017) as well as on research led search user interfaces for children (Gossen, Nitsche, & Nürnberger, 2012;Vanderschantz & Hinze, 2018), and in the home (e.g., Druin, Foss, Hutchinson, Golub, & Hatley, 2010), but little education or classroom based investigations of what and how children are interacting with technologies.…”
Section: Children's Information Seeking and Usementioning
confidence: 99%
“…An interaction model should support users during their use of the system and should align with the user"s mental model of how the system should work. Our interaction model is based on findings from interviews with NZ teachers and children (Vanderschantz et al, 2014b) and has been confirmed with observations of NZ children using Google (Vanderschantz & Hinze, 2017). Here we describe our interaction model by means of a conceptual wireframe design.…”
Section: Interaction Modelmentioning
confidence: 62%
“…The Related Searches offered by the search engine were seldom used by children in those studies. We also observed children having difficulty identifying which page they would like to visit and which pages they had already visited when reviewing a search engine results page list (Vanderschantz & Hinze, 2017). It was observed that children were unsure where factual information displayed in pull-boxes or sidebars on ISE"s came from and this compounded the effect of mistakenly visiting a website several times.…”
Section: Our Previous Contributionsmentioning
confidence: 86%
See 2 more Smart Citations